2014
DOI: 10.1167/iovs.14-14733
|View full text |Cite
|
Sign up to set email alerts
|

A Topographical Relationship Between Visual Field Defects and Optic Radiation Changes in Glaucoma

Abstract: A significant loss of OR fibers connected to the severely damaged part of the optic nerve head, but not the fibers connected to the relatively spared retinal hemifield shows a direct relationship between retinal neuronal damage and functionally connected OR fibers in glaucoma. However, OR fibers connected to the relatively preserved visual hemifield in the glaucoma subjects still showed changes in radial diffusivity compared with controls, suggesting possible early dysfunction. Our results support the notion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…28 The data consistently respect the topographical relationship between brain involvement and retinal neurodegeneration. 29 We detected regional GMV decrease in the anterior calcarine fissure of advanced POAG but not in early-moderate POAG. This is in agreement with a recent report of GM density changes in advanced, but not early POAG.…”
Section: Discussionmentioning
confidence: 60%
“…28 The data consistently respect the topographical relationship between brain involvement and retinal neurodegeneration. 29 We detected regional GMV decrease in the anterior calcarine fissure of advanced POAG but not in early-moderate POAG. This is in agreement with a recent report of GM density changes in advanced, but not early POAG.…”
Section: Discussionmentioning
confidence: 60%
“…Both anterograde and retrograde trans-synaptic degeneration in the visual system has been reported in several pathological conditions including ON [9,[26][27][28][29], glaucoma [30][31][32], ischaemic, surgical or traumatic occipital injury [33][34][35][36][37] and congenital homonymous hemianopia [38]. In addition, a number of recent cross-sectional studies have demonstrated a tract-specific association between OR damage and retinal thinning in patients with MS [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Visual deficits are usually not detected until there is significant loss of RGCs and their axons (Kaushik et al, 2014). Alterations in metabolic events, gene expression, and degeneration of RGC axonal anterograde and retrograde transport occur during the early stages of glaucoma (Della Santina et al, 2013).…”
Section: Basic Overview Of Visual Processingmentioning
confidence: 99%
“…Several investigators have conducted experiments in monkey models of experimental glaucoma to demonstrate the effect of increased IOP on neuronal morphology and neuron counts (Weber et al, 2000), dendritic changes (Gupta et al, 2007; Ly et al, 2011), as well as loss or shrinking of neurons in the LGN (Ito et al, 2009; Yucel et al, 2000; Yucel et al, 2001). There is a topographic relationship between RGC loss and/or damage and effects on the posterior visual pathway during glaucoma disease progression (Hayashi et al, 2013; Kaushik et al, 2014), where trans-synaptic degeneration is the major cause of wide-spread disease progression following initial RGC loss (Kaushik et al, 2014; Yucel and Gupta, 2008; Zhang et al, 2009). …”
Section: Basic Overview Of Visual Processingmentioning
confidence: 99%